Nursing Professional Training Mode Based on Internet Plus - Xiaojing Qiu, Songzeng Ren (Forest Chemicals Review, 2022)
With the popularity of mobile Internet, "Internet plus care" has gradually become the trend of nursing industry. Under the background of "Internet +", nursing talents are required to have the ability of personalized service customization, intelligent nursing construction and management and cross-border ability. This requires colleges and universities to carry out a new nursing talent training mode, including establishing the talent training goal under "Internet +" and integrating information literacy into the nursing curriculum system. Colleges and universities should introduce information-based teaching methods into nursing teaching process and constantly improve teachers’ information-based level. This paper studies the training mode of nursing talents under the background of "Internet +" and discusses the training mode. The results have a certain reference value for the training of nursing talents in the digital era.